(Mis)information and the politicization of food security. (1st April 2017) - Smyth, Stuart J.; Phillips, Peter W. B.; Castle, David
Abstract: With 20 years of genetically modified crop production, data supporting their benefits and safety abound yet the social battle regarding GM crops has not abated and, in fact, seems to have become even more vociferous. Environmental non-governmental organizations have effectively boxed themselves into a corner as they find themselves unable to acknowledge the science-based evidence of benefits and remain firmly committed in their opposition, contributing to campaigns of misinformation. Improved food security is being jeopardized given the rejection of science by the environmental movements, resulting in food security becoming a political issue.